The Motivation Stimulating Factors And The Orang Asli Students’ Motivation: Is There A Relationship? - et. al., Hamidah Yusof, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The focus of this study is to identify the relationship between the Motivation Stimulating Factors (MSFs) and the Orang Asli students’ motivation. This study is conducted based on teachers’s perception, and it involves 113 teachers who are teaching at 15 Orang Asli schools. Data are collected by using questionnaires and are analyzed by using descriptive statistics and inferences method. The findings of the study show that the level of both students’ motivation and motivating factors are relatively high. The relationship between the two focused factors also are observed to be positive and significant. Other than that, the motivation factors are observed to jointly and significantly influence the students’ motivation level. This study suggests that all motivating factors to be integrated to ensure that the motivation of Orang Asli students is continuously nurtured and maintain at a high level, in the mission to achieve academic excellence.